2014
DOI: 10.1111/jori.12040
|View full text |Cite
|
Sign up to set email alerts
|

Do the Better Insured Cause More Damage? Testing for Asymmetric Information in Car Insurance

Abstract: This article tests for the presence of asymmetric information in Dutch car insurance among senior drivers using several nonparametric tests based on conditional-correlation approach. Since asymmetric information implies that more comprehensive coverage is associated with higher risk, we examine whether the better insured have a higher frequency of claims or cause more severe accidents. Using data on claim occurrences, incurred losses and written premiums, and controlling for the insureds' experience rating, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Such mixed results have persisted over the years: Kim et al () found robust evidence of asymmetric information in South Korea; Shi, Zhang, and Valdez () found a significant positive relationship between coverage level and risk for experienced drivers in Singapore; Spindler, Winter, and Hagmayer () found evidence of asymmetric information in Germany; but Zavadil () found no evidence of asymmetric information in the Netherlands. These empirical inconsistencies suggest that asymmetric information may well have different impacts on different markets.…”
Section: Introductionmentioning
confidence: 99%
“…Such mixed results have persisted over the years: Kim et al () found robust evidence of asymmetric information in South Korea; Shi, Zhang, and Valdez () found a significant positive relationship between coverage level and risk for experienced drivers in Singapore; Spindler, Winter, and Hagmayer () found evidence of asymmetric information in Germany; but Zavadil () found no evidence of asymmetric information in the Netherlands. These empirical inconsistencies suggest that asymmetric information may well have different impacts on different markets.…”
Section: Introductionmentioning
confidence: 99%
“…The above competing models provide testable predictions on the temporal pattern of profits and consumer lock‐in that allow us to empirically examine the significance of information asymmetry. However, despite the large literature on empirical testing of adverse selection (see , Cohen and Siegelman, , Spindler et al., Winter, and Hagmayer, ; Zavadil, , among others for recent contribution), empirical work on asymmetric information in a dynamic context is not emerging in parallel with the theoretical development in multiperiod models. Some recent examples include Dionne et al.…”
Section: Introductionmentioning
confidence: 99%
“…Three articles focus on the role of asymmetric information in autoinsurance. Zavadil () tests for asymmetric information in autoinsurance among senior drivers in the Netherlands using the conditional‐correlation approach. The study detects no evidence of asymmetric information in this particular market, which is in contrast to most of the prior literature.…”
Section: Resultsmentioning
confidence: 99%